First experiences of communication with mechanically ventilated patients in the intensive care unit using eye-tracking technology. (2nd January 2023) - Ull, Christopher; Weckwerth, Christina; Schildhauer, Thomas Armin; Hamsen, Uwe; Gaschler, Robert; Waydhas, Christian; Jansen, Oliver
Abstract: Introduction: Eye-tracking (ET) may be a novel tool for communication with intubated and mechanically ventilated critically ill patients. We hypothesized that ET could be learned fast and be used successfully by intensive care unit (ICU) and intermediate care (IMC) patients with artificial airways for communication. Methods: Including all patients with mechanical ventilation via oral intubation or tracheostomy, who were at least 18 years of age with a score of −1 to +1 points on the Richmond agitation-sedation scale and a history of ventilation for more than 48 h. A commercially available ET was used. The investigations were performed by a physician with the support of a psychologist following a standardized study protocol. Results: During a 4-week period a total of 11 patients completed all of the five steps of our study protocol. The time to complete our study protocol was 64 ± 23.8 min (range 43–125 min) with a mean of 1.5 ± 0.9 sessions (range 1–4 sessions). Seven patients (63.6 %) could run through all of the five steps within their first session. All patients (100%) preferred the gaze fixation technique to control the ET to the wink control. Conclusion: Mechanically ventilated ICU and IMC patients are able to use ET in a very short time for communication to indicate their basic needs, answer rating scales and pain scores as well as questionnaires about quality of life and self-esteem. Implications for rehabilitation: COMFORT - The novel communication device improves the patients' ability to communicate with the attending physicians, physiotherapists and nurses in order to provide a tailored rehabilitation approach. COMPLIANCE - The use of the eye-tracking technology enables the patients to communicate special needs and fears during the course of the rehabilitation. COMPLICATIONS - The eye-tracking technology enables the attending rehabilitation team to earlier detect complications (e.g. pain, depression) during the course of the rehabilitation.